Detecting residual stress on toughened glass surface by two complementary interferometers. (7th January 2022) - Jia, Kangning; Liu, Shiyuan; Wan, Haopeng; Mao, Huade; Xu, Xiaodong; Zhou, Huijun; Gao, Wenli; Cheng, Liping; Yan, Xuejun; Zhang, Shuyi; Zhang, Xichen; Zheng, Heng; et al.
Abstract: Taking advantage of the birefringence of crystal, this paper proposes an effective optical system to detect the residual stress at the surface of toughened glass. A theoretical model based on matrix optics is built to describe the optical distribution of a probe light in the system, and the simulation outputs two complementary images whose mode patterns are determined by the phase delay arising from the surface-stress–induced birefringence. The experimental results confirm the simulation results that the mode pattern varies accordingly while the phase delay varies in 2 period. Features of interference fringes are extracted by dedicated image recognition algorithm and form their own feature data sets. Comparing the experimental data sets with the simulation ones, the phase delay of each experimental pattern can be deduced, so the stress of the sample point can be calculated. Our device's surface stress scanning results of toughened glass are very close to the commercial instrument SCALP-04's ones, with the relative deviation between them below 6%. Our system provides an efficient and simple way to measure present stress distribution on the surface of transparent materials, and owing to its fewer instruments involvement, broad detecting distance, and high signal-to-noise ratio, our system can be developed into integrated products. This method can also be applied in different materials such as high polymer, silicide, etc., where only the wavelength of the laser needs to be modified.